2016
DOI: 10.1007/s11746-016-2792-y
|View full text |Cite|
|
Sign up to set email alerts
|

Physicochemical and Rheological Characterization of Roll‐in Shortenings

Abstract: Overall, roll-in shortening differed from other samples in regard to molecular makeup but not greatly in their physical parameters, suggesting that triacylglycerol composition has important implications on their functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…, ZTC had a higher SFC at lower temperatures and lower SFC at higher temperatures in comparison with CM102, but they were not significantly different ( P > 0.05). These trends were in accordance with previous studies on the physicochemical characteristics of different types of shortenings (Ahmadi & Marangoni, ; Karabulut & Turan, ; Macias‐Rodriguez & Marangoni, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…, ZTC had a higher SFC at lower temperatures and lower SFC at higher temperatures in comparison with CM102, but they were not significantly different ( P > 0.05). These trends were in accordance with previous studies on the physicochemical characteristics of different types of shortenings (Ahmadi & Marangoni, ; Karabulut & Turan, ; Macias‐Rodriguez & Marangoni, ).…”
Section: Resultssupporting
confidence: 92%
“…However, based on the high level of stearic acid, palmitic acid, and TFA content, CM101 may contain hydrogenated soybean oil blended with palm oil or its derivatives, and due to the high level of palmitic acid and low level of TFA, CM102 may contain PS (Table ). In their physicochemical and rheological characterization of nine brands of roll in shortenings, Macias‐Rodriguez and Marangoni () reported that SFA content varies from 41 to 60% (w/w), and two out of nine shortenings contained 23–29% TFA, mainly elaidic and linoelaidic acids. Karabulut and Turan () also reported that the TFA content of 10 brands of shortening ranged from 2 to 16.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Shear was not only influencing crystal and platelet aggregation, but also the size of the platelets, the primary entities of the fat crystal network. Ultrasmall angle X‐ray scattering (USAXS) was used to study the structure of fat systems from the nanoscale to mesoscale (from 100 nm to 15 μm) (Macias‐Rodrigues and Marangoni, ; Peyronel et al, ). Processing impact on platelet size was confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…The geometries were fixed with adhesive 600 grit sandpaper to minimize slip during measurements. Samples were placed onto the lower plate and compressed between the plates with an axial force not exceeding 2N to avoid error, as overloading has been shown to modify the rheology ( Macias-Rodriguez and Marangoni, 2016a ). The parallel plates had temperature control by Peltier units located in the lower plate and the hood of the rheometer.…”
Section: Methodsmentioning
confidence: 99%